The Power Of Peer Voice: Evaluating The Effectiveness Of User-Generated Content In Shaping Gen Z’s Purchase Intentions (International Forum of Researchers and Lecturers, 2025)
The development of social media has changed how consumers, especially Generation Z, receive information and make purchasing decisions. One element that plays an important role in this process is User-Generated Content (UGC), which is content created by ordinary users, not by brands or companies. This study aims to evaluate the effectiveness of UGC in influencing Gen Z's purchase intention by examining seven main dimensions, namely Source Credibility, Content Quality, Emotional Appeal, Perceived Similarity, Engagement Level, Platform Trust, and UGC Frequency Exposure. The method used is a quantitative approach with a survey technique on 100 Gen Z respondents who are active on social media and have been exposed to UGC content related to products or services. Data were analyzed using multiple linear regression through the SPSS application to test the effect of each independent variable on the dependent variable, namely Purchase Intention. The results of the study showed that Platform Trust and UGC Frequency Exposure had a positive and significant effect on Gen Z's purchase intention. Conversely, Content Quality and Engagement Level showed a negative effect on purchase intention. Meanwhile, other variables such as Source Credibility, Emotional Appeal, and Perceived Similarity had a positive but insignificant effect. These findings confirm that trust in the platform and frequency of content exposure are more important determinants of Gen Z purchase intention than content quality or social interactions alone. The results are expected to provide strategic insights for marketers in designing more effective UGC-based campaigns to target the Gen Z segment.